Risk factors for poor bereavement outcomes and the support needs of adult bereaved refugees within the psychosocial-cultural concept of personhood: a systematic review - Çiğdem Fulya Dönmez; Çiğdem Fulya Dönmez; Muzeyyen Seckin; Cara Bailey (Frontiers in Public Health)
BackgroundThe majority of refugees are exposed to trauma and multiple deaths and often face difficulties in coping with the death of someone close to them. This review aimed to systematically synthesize evidence regarding the risk factors associated with poor bereavement outcomes and the support needs of refugees during bereavement, using the ring theory of personhood as a guiding framework to inform service provision and policy development.MethodsA systematic review was conducted using five citation databases (PsycINFO, CINAHL, SocINDEX, MEDLINE, and Web of Science), along with gray literature sources, to explore the bereavement support needs of refugees worldwide. The review followed the ring theory of personhood framework. A standardized data extraction tool (34) was used to analyse studies that included adult refugees who had experienced the death of a family member/friend. Two reviewers independently assessed the quality of the included studies to reduce bias. Due to the heterogeneity across the included studies, a narrative synthesis was conducted independently by two reviewers, with consensus reached on the final analysis.ResultsA total of 11 studies (eight quantitative, two mixed-methods, and one qualitative) were eligible for inclusion, representing a combined sample of 3,053 refugees. Across the rings of personhood, various risk factors related to bereavement were identified, including female sex, age, comorbidities, cultural and religious beliefs/values, and social factors. The findings indicate that refugees would benefit from culturally sensitive diagnostic tools for the early detection of grief symptoms, along with psycho-socio-cultural bereavement support interventions. Such interventions could enhance healthcare providers’ understanding of refugees’ perspectives, values, and preferences, thereby improving the quality of care provided.ConclusionThis review identified a wide range of culturally sensitive assessments and support needs for bereaved refugees. A personalized approach to bereavement assessment and care is recommended to facilitate a more comprehensive and existential understanding of bereavement and grief in research, clinical practice, policymaking, and community-based support systems. Further research is warranted to examine the long-term effects of bereavement on refugees’ mental health and to explore strategies for providing sustained support throughout the refugee journey.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022370126, Identifier CRD42022370126.